Unintended Consequences: Can the Rise of the Educated Class Explain the Revival of Protectionism? - Paolo E. Giordani; Fabio Mariani (Institute of Labor Economics (IZA), 2020)
This paper provides a rationale for the revival of protectionism, based on the rise of the educated class. In a trade model with heterogeneous workers and entrepreneurs, globalization generates aggregate gains but has distributional effects, which can be attenuated through taxation. By playing a two-stage political game, citizens decide on trade openness and the extent of redistribution. In this setting, trade liberalization is politically viable as long as the losers from trade are compensated through the redistributive mechanism. When skilled workers account for a large share of the population, however, there may be limited political support for redistribution, and those who are left behind by globalization – namely unskilled workers and importing-sector entrepreneurs – can form a coalition to impose protectionist measures. We then build a dynamic version of the model, where human capital accumulation is driven by public education. Our analysis suggests that globalization – by favoring the ascent of the educated class and thus eroding the political support for redistribution – may ultimately breed its own decline.
Keywords: D72; F68; I24; J24; O40; 330; trade; redistribution; political economy; human capital accumulation